Monetary incentives and the contagion of unethical behavior - Benoît Le Maux; David Masclet; Sarah Necker (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2021)
We analyze both theoretically and empirically how monetary incentives and information about others' behavior affect dishonesty. We run a laboratory experiment with 560 participants, each of whom observes a number from one to six with there being a payoff associated with each number. They can either truthfully report the number they see or lie about it in order to increase their payoff. We vary both the size of the payoff (Low, High, and Very High) and the amount of information about others' dishonesty (With and Without Information). We first find that dishonesty falls in the Very High treatment. Second, while social information has on average at most a weak positive effect, there is a strong effect if the accuracy of individuals' beliefs is accounted for. Third, social information and payoffs do not interact with each other.
Keywords: C91; D03; D78; 330; Laboratory experiment; theory; cheating; monetary incentives; information on others' behavior; lying costs